The impact of food and non-alcoholic beverage sponsorship and marketing in the school environment on the food choices of school-going children and adolescents: A scoping review 2011 – 2023 - Farmer, Kelly Odette (Stellenbosch University, 2025)
Globally, childhood obesity presents as a major public health challenge that is steadily on the increase. This is a result of, among other factors, children consuming excessive amounts of empty calories, specifically from foods high in saturated fats, sugar, and sodium, which is exacerbated by targeted marketing and sponsorships. The scoping review aimed to investigate the prevalence of food and non-alcoholic beverage marketing in schools and to determine the impact of marketing and sponsorship on the food choices of learners. The objectives of the scoping review were to conduct a systematic search of available and relevant literature, identify recurring themes and knowledge gaps within the literature and make recommendations for future research in this field of study. For this scoping review PubMed, Scopus, Web of Science, and EBSCO were searched for relevant studies published between 2011 – 2024. Grey literature was searched for on ProQuest and Google Scholar. The search occurred in February 2024 for studies that described school children, advertising, food preferences, and school environment. The results were exported from the online database into CADIMA for data analysis and screening. The total number of articles screened was 1608 references. The screening process was completed by two reviewers at the title and abstract stage and then at the full-text stage to determine eligibility for inclusion in the review. A total of twelve primary studies (n=12) were included in the final review. The evidence mapped out through this scoping review found that a link has been established between food and non-alcoholic beverage marketing and enhanced interest in these products from adolescents, although the traditional forms of advertising have become less relevant. It showed that food and non-alcoholic beverage marketing is prevalent in schools and influences the food preferences and consumption of learners. Additional contributing factors identified were availability, affordability, accessibility and peer influence. The findings also indicated that adolescents attending public schools were more likely to consume less healthy beverage options compared to peers in private schools. The recurrent themes that emerged from the evidence synthesis were food and non-alcoholic beverage marketing in the school food environment, sponsorship and brand awareness, food preference and food consumption of children and adolescents. Policymakers and other relevant stakeholders should focus on the school food environment as a setting and opportunity to positively influence children and adolescents' food choices and consumption habits. Furthermore, more research needs to be conducted in this field, primarily focusing on the internal school food environment. Future research may be broadened to assess the long-term impact of food and non alcoholic beverage marketing targeted at children and adolescents.